Aransemen Lagu Buku Ende No. 585 “Somba Ma Jahowa” Dalam Instrumen Taganing - Lamsa J Sihombing (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The aim of this research is to develop the song ''BE. 588 Somba Ma Jahowa Debata” into the Taganing arrangement and the motif in this song still uses the original melody from the song but there is a slight change in tempo from MM 120 to MM 98, and the rhythm aims to be more wise and pleasant to listen to. This research uses qualitative descriptive research, namely by describing the "Arrangement of Ende Book No. 585 Somba Ma Jahowa Debata" in the Taganing Instrument from December 2023 to April 2024. By conducting observations, literature and several sources related to the Taganing instrument and the congregation HKBP Bahal Batu 1 Resort Bahal Batu church, written and unwritten. The results of this research are Songs in the Ende Book No. 585 "Somba Ma Jahowa Debata" is a very wise song and has meaning and message in its poetry. This thesis discusses the presentation and arrangement process of Taganing in the song in Ende's book No. 585 "Somba Ma Jahowa Debata" accompanying Sunday worship at the HKBP Bahal Batu 1 Resort Bahal Batu church. For the time signature the author uses a 4/4 time signature following the original score of the song and the basic note G = do and with a tempo of Moderato MM 98